Mistrust An Ethnographic Theory - Carey, Matthew (Malinowski Monographs, 2017)
Trust occupies a unique place in contemporary discourse. Seen as both necessary and good, it is variously depicted as enhancing the social fabric, lowering crime rates, increasing happiness, and generating prosperity. It allows for complex political systems, permits human communication, underpins financial instruments and economic institutions, and holds society itself together. There is scant space within this vision for a nuanced discussion of mistrust. With few exceptions, it is treated as little more than a corrosive absence. This monograph, instead, proposes an ethnographic and conceptual exploration of mistrust as a legitimate epistemological stance in its own right. It examines the impact of mistrust on practices of conversation and communication, friendship and society, as well as politics and cooperation, and suggests that suspicion, doubt, and uncertainty can also ground ways of organizing human society and cooperating with others.